Demyelination in Diabetic Distal Symmetric Polyneuropathy: A Retrospective Electrodiagnostic Study - Roopa Sharma; Iqra Faiz; Ahmed Sabra; Kazzim Jaffry; Nizaar Souayah; Machteld E. Hillen (Journal of Clinical Neuromuscular Disease, 2026)
Abstract Background: Features of acquired demyelination have been reported in diabetic distal symmetrical polyneuropathy (DDSP). Objectives: To characterize the natural history of demyelination in diabetic distal symmetric polyneuropathy (DDSP). Methods: We retrospectively reviewed serial motor nerve conduction studies in 71 patients with DDSP with ≥2 electrodiagnostic sessions. Patients were categorized as G1 [no new conduction velocity slowing (CVS)], G2 (new CVS), or G3 (new CVS in the demyelinating range per American Academy of Neurology criteria). Age, body mass index, hemoglobin A1c (HbA1c), and study intervals were compared between groups. Results: The cohort included 30 men and 41 women. The mean age and time between the first and most recent studies were 55.91 ± 10.44 years and 32 ± 31 months, respectively. HbA1c was available in 57 patients (mean 7.87 ± 2.61). At the patient level, 30 of 71 (42.2%) had new CVS in ≥1 nerve; among these, 12 of 30 (40.0%) involved a single nerve, 10 of 30 (33.3%) involved 2 nerves, and 8 of 30 (26.7%) involved 3 or more nerves. Demyelinating-range CVS was present in 5 of 30 (16.6%) of those with CVS, corresponding to 5 of 71 (7.0%) of the entire cohort. When stratified by group (Table 2), mean HbA1c differed significantly between G2 and G3 (8.14 ± 2.48 vs. 10.56 ± 5.25; P < 0.05) (Table 4) and between G1 and G3 (7.48 ± 2.21 vs. 10.56 ± 5.25; P < 0.002) (Table 5), while age, body mass index, and interstudy interval showed no significant differences (Tables 3–5). Conclusions: In a subgroup of patients with DDSP, an evolving compound motor action potential independent motor nerve CVS, interval prolongation of the distal motor latency, and interval prolongation or absence of F waves may occur, consistent with a superimposed acquired demyelination. These changes were more frequently identified in patients with higher mean HbA1c values.